1996
DOI: 10.1557/proc-449-471
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal Growth Hillocks in GaN Epilayers

Abstract: We describe a study of the hexagonal growth hillocks commonly present in gallium nitride films. The MOVPE-grown epilayers of the present work exhibit a predominantly smooth morphology but small groups of hexagonal hillocks were found to populate the surface, particularly at the sample edges.Scanning electron (SE) micrographs were taken of several groups of hillocks. At the maximum beam energy of 25 keV, two types of hexagonal hillock are visible. Hillocks in the first group are terminated by an apex (ie. they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…6. If our assessment is correct, however, the Gaterminated surface can have a significantly higher growth rate than a N-terminated surface, in agreement with the speculations of Middleton et al 24 The growth rate differential is also consistent with recent results on MOCVD GaN reported by Liliental-Weber et al, 25 where ͑0001 គ͒-oriented IDs grow at a slower rate than the ͑0001͒-oriented matrix, leading to oriented ''pits'' that could be described as inverted hillocks. The IDBs were along the ͕101 គ0͖ planes, similar to IDs found in other films grown by MBE 7,15 and MOCVD.…”
Section: Inversion Domains and Surface Morphologysupporting
confidence: 90%
“…6. If our assessment is correct, however, the Gaterminated surface can have a significantly higher growth rate than a N-terminated surface, in agreement with the speculations of Middleton et al 24 The growth rate differential is also consistent with recent results on MOCVD GaN reported by Liliental-Weber et al, 25 where ͑0001 គ͒-oriented IDs grow at a slower rate than the ͑0001͒-oriented matrix, leading to oriented ''pits'' that could be described as inverted hillocks. The IDBs were along the ͕101 គ0͖ planes, similar to IDs found in other films grown by MBE 7,15 and MOCVD.…”
Section: Inversion Domains and Surface Morphologysupporting
confidence: 90%
“…Cathodoluminescence (CL) imaging has emerged as an important technique for acquiring very high-resolution images of nitride layers [5,6], with the capability to obtain a vast amount of information from thin semiconductor layers. Panchromatic images can 160 K. P. O'Donnell et al Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CL observations have revealed that the hillocks present specific recombination properties related to their structural features. Middleton et al 1 found enhanced yellow emission in the center of pyramidal hillocks and related it to defects associated with inversion domain boundaries. Herrera Zaldivar et al 2 reported a marked CL contrast at the center and at the border of round shaped hillocks that was explained by an inhomogeneous distribution of point defects and impurities.…”
Section: Study Of Growth Hillocks Inmentioning
confidence: 99%